THE SOCIAL CONSTRUCTION OF GENDER FEMALE CANNIBALISM IN PAPUA NEW GUINEA (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
In Papua New Guinea, gender identity has been described as strict segregation and oppression of women. However, cannibalism can give us new insights into a gender identity. Culture creates boundaries that imply division, though “sameness” is experienced. This social experience is projected onto the body. In the act of cannibalism, substance and power are exchanged. Gender identity reflects then an ideology, not a body function.
Keywords: cannibalism; gender; substance; power; sameness and difference